Przesłanki rozwoju metod zarządzania - Ćwiklicki, Marek (The Reasons of Management Methods' Development, 2006)
In the article, the basic issues of management methods creation were described. First, the reasons of their elaboration were presented, together within the answer given to the question: why the methods appear? Next, the short scheme of management precursors is given. The part contains the description of F.W. Taylor, K. Adamiecki, S. Shingo and T. Ohno. The last issue were different conditions that facilitate the management method development. At the end, the correlation were drawn to the J. Schumpeter's concept innovation change.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 41-46